Hydrothermally synthesised NiCoP nanostructures and electrospun N-doped carbon nanofiber as multifunctional potential electrode for hybrid water electrolyser and supercapatteries. (10th February 2019) - Surendran, Subramani; Shanmugapriya, Sathyanarayanan; Zhu, Pei; Yan, Chaoyi; Vignesh, Ramasamy Hari; Lee, Yun Sung; Zhang, Xiangwu; Selvan, Ramakrishnan Kalai
Abstract: In this work, a facile single-step hydrothermal technique is used to prepare a spherically concomitant foamy NiCoP as positrode for supercapatteries. Similarly, the nitrogen-doped carbon nanofibers are prepared by simple electrospinning technique to use as negatrode. The prepared materials are raptly examined through primary studies for both energy conversion and storage applications. Fascinatingly, NiCoP electrode encourages oxygen evolution reaction, and the carbon nanofiber electrode emboldens hydrogen evolution reaction with the minimum overpotential of 257 mV and 160 mV, respectively. In addition, a supercapattery is designed and operated at a full voltage window of 1.6 V using the fusion of carbon nanofiber as the negatrode and the cutting-edge NiCoP as the positrode, which presents a superior energy (56 Wh kg −1 ) and an improved power density (5333 W kg −1 ) with a long cyclic stability (5000 cycles). Finally, the fabricated supercapattery device is used to power the constructed hybrid water electrolyser that requisites a low cell voltage of 1.71 V to afford a current density of 10 mA cm −2 . Overall, the prepared electrodes reveal its superiority of handling the multifunctional challenges for both water electrolyzer and supercapatteries.